Desain Game Edukasi Berbasis Board Game Sebagai Media Pembelajaran Inovatif Untuk Siswa Sd Kristen Banjarsari - Shaneabel Azarya Utomo Setyo Budi Utomo; Ahmad Khoirul Anwar; Evelyne Henny Lukitasari (Universitas Sahid Surakarta, 2026)
Elementary school is the initial level of education that plays a crucial role in shaping children's cognitive development, learning habits, and character. However, learning at Banjarsari Christian Elementary School of Surakarta is still dominated by conventional methods that are inappropriate to the developmental characteristics of elementary school students, resulting in low student interest and focus. Questionnaires administered to fourth- to sixth-grade students and their parents and guardians indicate that students often become bored, lose focus, and have difficulty understanding the learning material. On the other hand, Banjarsari Christian Elementary School excels in its application of humanistic Christian values, child-friendly learning environment, and close relationships between teachers and students, thus offering potential for development through learning innovation. This study aims to design educational learning media to support the learning process at Banjarsari Christian Elementary School of Surakarta. The media design is an educational board game with a visual and interactive approach, using the ADDIE method. The design is expected to increase student interest, focus, and engagement in learning.